THE INVASIVE ARMORED SUCKERMOUTH CATFISH PTERYGOPLICHTHYS PARDALIS (SILURIFORMES: LORICARIIDAE) AS PART OF THE DIET OF THE DOUBLE-CRESTED CORMORANT PHALACROCORAX AURITUS (PHALACROCORACIDAE) IN TWO TROPICAL REGIONS OF MEXICO - Rodríguez-Santiago, María Amparo (2018)
Th e armored suckermouth catfi sh Pterygoplichthys pardalis (Castelnau 1855) is an invasive fi sh species in several regionsin Mexico, including the fl uvial lagoon systems of the state of Campeche in southeastern and in Mazatlán, Sinaloa innorthwestern of the country. Although several studies have mentioned the negative impacts of this invasive fi sh in theaquatic environment, few reports exist about the natural predators that may help to control these fi sh populations. Inthis study, we investigate the feeding predation by double-crested cormorants Phalacrocorax auritus (Lesson, 1831) onP. pardalis in the Palizada River, southeast of the Gulf of Mexico, and in the the Laguna del Camarón in northwesternMexico. Th e evidence of feeding found in stomach contents of these birds indicates that feeding habits might beingadapted to changes in the resident fi sh community after the introduction of armored suckermouth invasive catfi sh to thisnew aquatic environments, with the birds exploiting a new food source as a component of their diet.